MENINGKATKAN KEMAMPUAN MENGENAL ANGKA MELALUI PERMAINAN SMART HEAD ANAK USIA DINI DI TK ABA 32 AMPELGADING DAMPIT-MALANG - Antika, Aisyah Nindi; Hikmah, Fitrotul (Program Studi Pendidikan Islam Anak Usia Dini (PIAUD), 2024)
Children's cognitive abilities in early childhood tend to be lacking due to the ineffectiveness and appropriateness of the learning methods used by teachers. The purpose of this study is to describe the implementation or application of the Smart Head game in ABA 32 Ampelgading Kindergarten. This study uses the Classroom Action Research (CAR) method consisting of cycle I and Cycle II which are implemented in ABA 32 Ampelang Kindergarten. This study has 4 stages, namely planning, implementation, observation, and reflection. Data are obtained through observation results and children's test score data. Data collection techniques use interviews, observation, and documentation. Data analysis techniques include qualitative and quantitative data. The results of the study showed that in cycle I the ability to recognize numbers in children was still low, but after implementing the Smart Head game in cycle I for 3 meetings, a percentage of 49.2% was obtained. For children's ability to recognize numbers, there has been an increase but it is still below average. Because in cycle I it still has not reached the average, it is continued to cycle II. In cycle II which was implemented for 3 meetings, there was an increase in the percentage of 100%. It can be concluded that cycle I and cycle II experienced an increase, so there was an increase in the ability to recognize numbers in early childhood through the Smart Head game at ABA 32 Ampelang Kindergarten with a percentage of 100% with very good criteria.